2022
DOI: 10.3389/fimmu.2021.828858
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Risk Factors for Acute Radiation Pneumonitis in Patients With Prior Receipt of Immune Checkpoint Inhibitors

Abstract: PurposeDosimetric parameters (e.g., mean lung dose (MLD), V20, and V5) can predict radiation pneumonitis (RP). Constraints thereof were formulated before the era of combined immune checkpoint inhibitors (ICIs) and radiotherapy, which could amplify the RP risk. Dosimetric predictors of acute RP (aRP) in the context of ICIs are urgently needed because no data exist thus far.Methods and MaterialsAll included patients underwent thoracic intensity-modulated radiotherapy, previously received ICIs, and followed-up at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
5
1
Order By: Relevance
“…It is convinced that the synergistic effect of TRT and ICI is strong, careful consideration and close monitoring of pneumonitis are needed for patients with previous treatment-related pneumonitis evoked by either TRT or ICI. However, we did not observe high incidence of pneumonitis among patients with antecedent ICI before TRT, while a small-size, single-arm retrospective study showed a relative high rate of G3+ RP (22.5%) in patients with prior ICI ( 32 ). Dosimetric variables were also not associated with G2+ or G3+ treatment-related pneumonitis in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…It is convinced that the synergistic effect of TRT and ICI is strong, careful consideration and close monitoring of pneumonitis are needed for patients with previous treatment-related pneumonitis evoked by either TRT or ICI. However, we did not observe high incidence of pneumonitis among patients with antecedent ICI before TRT, while a small-size, single-arm retrospective study showed a relative high rate of G3+ RP (22.5%) in patients with prior ICI ( 32 ). Dosimetric variables were also not associated with G2+ or G3+ treatment-related pneumonitis in this study.…”
Section: Discussioncontrasting
confidence: 80%
“…Chemotherapy, as a signi cant risk factor for predicting radiation pneumonitis, is consistent with the results of this study [16].There is still controversy regarding the correlation between dosimetric parameters and the occurrence of radiation pneumonitis. The study by Jianping Bi et al concluded that the mean lung dose (MLD) is the most critical dose-volume parameter in uencing radiation pneumonitis, and it can better prevent the occurrence of radiation pneumonitis in patients undergoing combined immunotherapy and radiotherapy [20].On the other hand, Zhe Ji et al…”
Section: Discussionmentioning
confidence: 99%
“…Most of them reported the recalled RP in patients receiving ICI after cCRT ( 21 , 23 , 24 ). Bi et al reported pneumonitis in patients receiving ICI before radiation ( 22 ). The RP of grade ≥2 was present in 40% (16/40) patients, and that of grade ≥3 was 22.5% (9/40), but it also did not compare to the chemoradiation group.…”
Section: Discussionmentioning
confidence: 99%